Prognostic impact of right ventricular mass change in patients with idiopathic pulmonary arterial hypertension. (1st April 2020) - Grapsa, Julia; Tan, Timothy C.; Nunes, Maria Carmo Pereira; O'Regan, Declan P.; Durighel, Giuliana; Howard, Luke S.G.E.; Gibbs, J. Simon R.; Nihoyannopoulos, Petros
Abstract: Background: Compensatory remodelling i.e. increased right ventricular (RV) mass frequently occurs as an adaptive response to the chronic pressure overload to maintain contractile function. The prognostic value of the serial change in RV mass is unclear. Aim: The aim of our study was to examine the longitudinal changes in RV mass and survival in patients with idiopathic pulmonary arterial hypertension (IPAH). Methods: Consecutive newly diagnosed IPAH patients >18 years old were prospectively recruited from a tertiary referral center. All recruited patients were maintained on guideline-based therapy and were followed up with echocardiography and cardiac magnetic resonance for 2 years. Results: Serial measures of RV mass revealed that survivors appeared to have had a compensatory increase in RV mass, which constituted adaptive RV remodelling early in the disease process, which was not seen in those who died. (Hazard ratio of 0.932, 95% confidence interval 0.893–0.973, p = 0.001). Conclusion: This study shows that serial measurement of RV mass in IPAH patients provides prognostic information. RV mass regression is an ominous prognostic sign, which may predict early mortality in these patients. Highlights: Thirty consecutive IPAH patients were prospectively recruited. The endpoint of the study was death. Regression of RV mass was an independent predictor of death.